1977
DOI: 10.1042/bj1630103
|View full text |Cite
|
Sign up to set email alerts
|

Proteoglycan populations of baboon (Papio papio) articular cartilage. Gel-electrophoretic analysis of fractions obtained by densitygradient centrifugation and by sequential extraction

Abstract: 1. Gel electrophoresis of proteoglycans extracted with use of 4 M-guanidinium chloride from baboon (Papio papio) articular cartilage and purified on DEAE-cellulose in 8 M-urea yielded three bands on electrophoresis in polyacrylamide/agarose gels: two wide bands close together (I and II) and a third, thinner and more rapidly moving band (III). 2. Gel electrophoresis of fractions from direct 'dissociative' gradients showed that these bands were partially separated (buoyant density of I greater than II greater th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
15
0

Year Published

1979
1979
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 55 publications
(15 citation statements)
references
References 36 publications
0
15
0
Order By: Relevance
“…Cartilage proteoglycans are markedly polydisperse with respect to Mr and chemical composition (Muir & Hardingham, 1975). Agarose/acrylamide-gel-electrophoretic separations, however, have demonstrated that this apparent polydispersity is due, in part, to the contribution of at least two structurally distinct populations (McDevitt & Muir, 1971;Roughley & Mason, 1976;Stanescu et al, 1977;Bayliss & Ali, 1978;Roughley & White, 1980, 1983Heinegard et al, 1985). Immunological (Wieslander & Heinegaord, 1981;Brennan et al, 1983;Heinegard et al, 1985) and biosynthetic studies (Triphaus et al, 1980) support the concept of proteoglycan heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…Cartilage proteoglycans are markedly polydisperse with respect to Mr and chemical composition (Muir & Hardingham, 1975). Agarose/acrylamide-gel-electrophoretic separations, however, have demonstrated that this apparent polydispersity is due, in part, to the contribution of at least two structurally distinct populations (McDevitt & Muir, 1971;Roughley & Mason, 1976;Stanescu et al, 1977;Bayliss & Ali, 1978;Roughley & White, 1980, 1983Heinegard et al, 1985). Immunological (Wieslander & Heinegaord, 1981;Brennan et al, 1983;Heinegard et al, 1985) and biosynthetic studies (Triphaus et al, 1980) support the concept of proteoglycan heterogeneity.…”
Section: Introductionmentioning
confidence: 99%
“…The extreme polydispersity has hampered attempts to identify subpopulations. Nevertheless there are indications that more than one population of proteoglycans is present in cartilage, especially as electrophoresis of proteoglycans on agarose/polyacrylamide gels shows two or three bands (McDevitt & Muir, 1971;Pearson & Mason, 1977;Stanescu et al, 1977). Considering the polydispersity of the proteoglycans, these bands are surprisingly sharp.…”
mentioning
confidence: 99%
“…Cartilage proteo-1959;Anderson et al, 1964;Mathews & Glasgov, glycans are complex polydisperse macromolecules 1966; Hjertquist & Engfeldt, 1967, and references consisting of chondroitin sulphate, keratan sulphate cited therein; Greiling & Stuhlsatz, 1969; Bjelle et (Rosenberg et al, 1975(Rosenberg et al, , 1976Hardingham et al, al., 1972;Hjertquist & Lemperg, 1972;Hjertquist & 1976;Heinegard & Axelsson, 1977; Heinegird, Wasteson, 1972;Lemperg et al, 1974;Mankin & 1977; Hascall & Heinegard, 1979) and oligo-saccharide side chains covalently linked to a protein core . Several studies (Hoffman et al, 1975;Hopwood & Robinson, 1975;Roughley & Mason, 1976;Stanescu et al, 1977;Swann et al, 1979) have also shown that articular cartilage contains different types of proteoglycans and significant quantities of protein and glycoprotein constituents. There is therefore the possibility that the gross chemical changes may reflect alterations in the structure and/or the proportions of the different types of macromolecular components.…”
mentioning
confidence: 99%